Effect of a thermoascus aurantiacus thermostable enzyme cocktail on wheat bread quality - Oliveira, D. S. [UNESP]; Telis-Romero, J. [UNESP]; Da-Silva, R. [UNESP]; Franco, C. M L [UNESP] (Elsevier, 2014)
Thermophilic fungus Thermoascus aurantiacus (CBMAI 756) on solid-state fermentation using corncob as a nutrient source produces an enzyme pool with the potential to be used in bread making. In this paper, the use of this enzyme cocktail as a wheat bread improver was reported. Both products released by flour arabinoxylan degradation and bread quality were investigated. The main product released through enzyme activity after prolonged incubation was xylose indicating the presence of xylanase; however, a small amount of xylobiose and arabinose also confirmed the presence of xylosidase and α-L- arabinofuranosidase, respectively. Enzyme mixture in vitro mainly attacked water-unextractable arabinoxylan contributing to beneficial effect in bread making. The use of an optimal enzyme concentration (35 U xylanase/100 g of flour) increased specific volume (22%), reduced crumb firmness (25%), and reduced amylopectin retrogradation (17%) during bread storage. In conclusion, the enzyme cocktail produced by T. aurantiacus CBMAI 756 can improve wheat bread quality. © 2013 Elsevier Ltd.
Keywords: Amylopectin retrogradation; Arabinoxylan; Bread staling; Crumb firmness; Thermoascus aurantiacus CBMAI 756; Xylanase